1999
DOI: 10.1248/bpb.22.268
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Herpes Simplex Virus Activity of Alkaloids Isolated from Stephania cepharantha.

Abstract: By screening water and MeOH extracts of 30 Chinese medicinal plants for their anti-herpes simplex virus (HSV)-1 activity, a MeOH extract of the root tubers of Stephania cepharantha HAYATA showed the most potent activity on the plaque reduction assay with an IC50 value of 18.0 microg/ml. Of 49 alkaloids isolated from the MeOH extract, 17 alkaloids were found to be active against HSV-1, including 13 bisbenzylisoquinoline, 1 protoberberine, 2 morphinane and 1 proaporphine alkaloids, while benzylisoquinoline and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 2 publications
2
19
0
Order By: Relevance
“…AZT, a nucleoside analog was originally designed to treat cancer and was the first approved drug for the treatment of AIDS through the mechanism of inhibiting reverse transcriptase [11]. FK3000 is a morphinan type alkaloid reported to have anti-herpes simplex virus activity in vitro and in vivo [12]. Though oleanolic acid (1) itself showed appreciable cytotoxicity on the tumor cell line, neither its FK3000 conjugates (25-26) nor the AZT conjugates (27-29) showed cytotoxicity at a concentration as high as 100 g/ml.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…AZT, a nucleoside analog was originally designed to treat cancer and was the first approved drug for the treatment of AIDS through the mechanism of inhibiting reverse transcriptase [11]. FK3000 is a morphinan type alkaloid reported to have anti-herpes simplex virus activity in vitro and in vivo [12]. Though oleanolic acid (1) itself showed appreciable cytotoxicity on the tumor cell line, neither its FK3000 conjugates (25-26) nor the AZT conjugates (27-29) showed cytotoxicity at a concentration as high as 100 g/ml.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Aporphine alkaloid, (+)-isocorydine -N-oxide (27) was isolated from the ethanolic extract of the stem bark of plant Miliusa velutina growing in Bangladesh (Hasan 2000). Isocorydine was identified from many other plants (Ribar 2003;El-Sawi and Motawe 2003;Goeren et al 2003;Mat 2000), and shown antiviral activity against HSV-1 (Nawawi et al 1999). Alkaloid (27) was found in plant Glaucium corniculatum from Egypt, and other glaucentrine N-oxide (28) (known as (+)-corydine N-oxide) (Al-Wakeel et al 1995).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To date, the isolation of only five stephaoxocanes (1bϪf) has been reported, their source being plants of the Menispermaceae family employed in folk medicine. [6,7] Stephaoxocanidine (1b, isolated from Stephania cepharantha) and eletefine (1c, which occurs in Cissampelos glaberrima, better known as C. pareira), have fully unsaturated AB rings, whereas their congeners stephaoxocanine 1d, eccentricine 1e, and N-methyleccentricine 1f display dihydro and tetrahydro-substituted AB ring systems, respectively. Most noteworthy is the fact that the stephaoxocanes bear a close structural relationship to other tetracyclic isoquinoline derivatives, such as the tropoloisoquinolines grandirubrine 2a and imerubrine 2b, and the azafluoranthenes, exemplified by telitoxine 3a and imeluteine 3b.…”
Section: Introductionmentioning
confidence: 99%